CALCULATION OF THE ALTITUDE DISTRIBUTION OF STRATOSPHERIC OZONE OVER KYRGYZSTAN BASED ON GROUND-BASED MICROWAVE MEASUREMENTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents the principles of reception and propagation of radiation from the rotational transition of ozone molecules at terahertz frequencies used in the observatory. Both methods of microwave measurements with absolute and atmospheric calibrations are given. The results of ground-based measurements for absolute calibration correspond to the measurement data of orbital instruments, the reference data. The correlation coefficient was selected based on atmospheric calibration.The results of calculations based on measurement data for average values of the seasonal variation of ozone content are presented. For clarity, the seasonal variation of ozone content over northern Kyrgyzstan over the past year is shown in comparison with the year of the first measurements at the observatory. As usual, a spring maximum and autumn minimum in ozone content are observed, typical for mid-latitudes.
Keywords: stratospheric ozone, absolute calibration, measurement, frequency, millimeter waves, radiation